2020
DOI: 10.1002/smtd.202000588
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Metal Oxides in Perovskite Solar Cells: Present and Future

Abstract: In recent years, the development of perovskite solar cells (PSCs) is advancing along the way, and the efficiency is comparable to traditional silicon‐based solar cells. However, as crucial factors in the road to commercialization, stability and upscaling manufacture have not been fully investigated yet. To solve these problems, the exploration of charge transport layer (CTL) is clearly imminent, which is critical to the stability of PSCs. Among them, inorganic metal oxides have better stability than organic CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…ALD is an attractive deposition method due to its excellent conformality, reproducibility, and industrial viability . Moreover, ALD as a deposition method has been used extensively in the field of perovskite PV, alone or in combination with buffer layers. ALD metal oxides not only serve as charge transport layers but also can be used as protective layers to prevent perovskite degradation especially from oxygen and humidity. Thus, ALD NiO layer can create a universal surface chemistry for SAM formation, which is independent of the pretreatment of ITO surface and ITO’s intrinsic properties.…”
Section: Introductionmentioning
confidence: 99%
“…ALD is an attractive deposition method due to its excellent conformality, reproducibility, and industrial viability . Moreover, ALD as a deposition method has been used extensively in the field of perovskite PV, alone or in combination with buffer layers. ALD metal oxides not only serve as charge transport layers but also can be used as protective layers to prevent perovskite degradation especially from oxygen and humidity. Thus, ALD NiO layer can create a universal surface chemistry for SAM formation, which is independent of the pretreatment of ITO surface and ITO’s intrinsic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Beside spin-coating as a solution method, atomic layer deposition (ALD) has become an effective technique to form dense thin films at low temperature on the various substrates with excellent thickness accuracy and conformality. [45,46] In this method, the thickness of desired layers is controlled by altering the number of specified reaction cycles. Here, we conducted ALD process using niobium pentoxide Nb(OEt) 5 precursor under the water vapor at 300 °C to deposit an ultrathin Nb 2 O 5 layer on the surface of ms-TiO 2 ETL (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the precise control at the atomic level, the high-quality lm of metal oxides has the merits of promoting charge transfer, suppressing the degradation caused by the external environment and internal ionic migration, and enhancing the photoelectric properties of the device. 133,134 Lee and co-workers prepared planar SnO 2 -based PSCs using ALD by modulating the deposition and post-annealing temperatures. It was found that the post-annealing process can effectively passivate the perovskite and SnO 2 interface, leading to reduced charge recombination.…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%